1988
DOI: 10.1017/s0021932000006702
|View full text |Cite
|
Sign up to set email alerts
|

Bedtimes and Sleep Duration in Relation to Smoking Behaviour in 14-year-old English Schoolchildren

Abstract: SummaryData from a survey of 3727 14-year-old children from 31 secondary schools in England in 1984–85 were analysed to obtain information about smoking habits, bedtimes and times of rising in the morning, on a weekday during school term. Subjects completed a questionnaire, anonymously, in class. Twenty percent of respondents reported that they currently smoked cigarettes. Smokers went to bed significantly later, and spent significantly less time in bed, than non-smokers. Twice as many smokers as non-smokers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
11
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 8 publications
(12 reference statements)
2
11
0
Order By: Relevance
“…Hygiene behaviours, either general or oral, were practiced more frequently by girls than by boys. This is consistent with the results of the European Health Behaviour School‐Aged Children study and other studies which reported that girls are generally cleaner than boys (7, 13–21). As mentioned earlier, avoiding infection and dirt may explain this phenomenon (12).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Hygiene behaviours, either general or oral, were practiced more frequently by girls than by boys. This is consistent with the results of the European Health Behaviour School‐Aged Children study and other studies which reported that girls are generally cleaner than boys (7, 13–21). As mentioned earlier, avoiding infection and dirt may explain this phenomenon (12).…”
Section: Discussionsupporting
confidence: 92%
“…These results agree with the few studies in developed countries that have examined the association between oral hygiene behaviours and general hygiene behaviours. This suggests that the association may be universal as it appears to apply in both developed and developing countries and during different decades (7, 14, 15, 18, 23).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Subjects living with less than 5 family members were more pertinent in tooth brushing behavior than were the subjects living together with many family members, in coincidence with observations among Japanese rural population (6). A significant effect of the parental characteristics on regular visit to dentist has been reported (17) and studies among English (18) and Scottish school children (2) found that lifestyle influence the tooth brushing practice in adolescents. The present study also showed relation of social activity (social volunteer work) with dental health behavior, the individuals who volunteer social work rarely were less likely to brush their teeth twice daily and use extra cleansing devices but were more likely to visit dentist.…”
Section: Discussionmentioning
confidence: 59%